2007
DOI: 10.1103/physrevb.76.054409
|View full text |Cite
|
Sign up to set email alerts
|

Physics of complex transverse susceptibility of magnetic particulate systems

Abstract: Complex transverse susceptibility is a recent proposed method for the determination of anisotropy and volume distributions in particulate magnetic media. So far, only thermal fluctuations and rate-dependent damped dynamics of the magnetic moment have been identified as reasons for the existence of the imaginary transverse susceptibility. In this paper, we apply a more general approach to derive the complex transverse susceptibility, and we show that the hysteresis phenomenon is the most general concept behind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…We are therefore most interested in the quantity as a function of H DC where is the transverse susceptibility at the saturating field H sat . In accordance with Aharoni et al's theoretical predictions [31], as well as other TS models [32,33], we observe maxima in the TS scan at the positive and negative anisotropy fields of the material, ±H K , and at the switching field, H S , for a unipolar sweep of the DC field from positive to negative saturation. This technique has been used with great success to examine the anisotropic magnetic properties of a variety of systems from multilayered thin films [34] to single crystals [35] and nanoparticles [36,37].…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…We are therefore most interested in the quantity as a function of H DC where is the transverse susceptibility at the saturating field H sat . In accordance with Aharoni et al's theoretical predictions [31], as well as other TS models [32,33], we observe maxima in the TS scan at the positive and negative anisotropy fields of the material, ±H K , and at the switching field, H S , for a unipolar sweep of the DC field from positive to negative saturation. This technique has been used with great success to examine the anisotropic magnetic properties of a variety of systems from multilayered thin films [34] to single crystals [35] and nanoparticles [36,37].…”
Section: Methodssupporting
confidence: 92%
“…This technique has been used with great success to examine the anisotropic magnetic properties of a variety of systems from multilayered thin films [34] to single crystals [35] and nanoparticles [36,37]. However it also lends itself particularly well to the rich physics involved in complex oxide systems to examine the unusual magnetic behavior often seen in manganites [28,32,35,39] and, as we show here, cobaltites.…”
Section: Methodsmentioning
confidence: 95%
“…In the TS method, as the DC field is swept from positive saturation to negative saturation of the sample under study, the resonant frequency of the coil with the sample changes proportional to the transverse susceptibility of the sample as follows: where transverse susceptibility at a saturation field H sat . It has been theoretically shown that a ferromagnetic material should yield TS peaks at the anisotropy fields (± H k ) and switching fields (− H S ) as the DC field is swept from positive to negative saturation and vice versa 26 , 27 . However, in some cases where H K values are very close to H S , the switching peak is often merged with one of the anisotropy peaks in a unipolar scan of the field for example from to positive to negative saturation.…”
Section: Resultsmentioning
confidence: 99%
“…Throughout this paper, we assume that the frequency f = ω/2π is significantly smaller than the ferromagnetic resonance frequency of F. For h ac transverse to H dc , the magnetization M of F is expected to oscillate, following the direction of the total field H dc + h ac (t). The transverse ac magnetic susceptibility χ T can be defined as the ratio of the amplitude of the ac magnetization component to the amplitude of the ac field [18,19,23]. However, in practice, a lockin technique is utilized to measure the ac magnetization, providing the (generally complex) harmonics M…”
Section: Ii1 Transverse Magnetic Ac Susceptibilitymentioning
confidence: 99%